SPACE COOLING WITH GROUNDWATER PUMPED BY A SOLAR DRIVEN PUMP - Dumrul, Hakan; Selimli, Selcuk; Yilmaz, Sezayi; Korkmaz, Baris (Konya Teknik Univ, 2023)
In this study, it was experimentally investigated that the groundwater of a well is brought to the surface using solar energy, which is one of the renewable energy sources, and the cooling of a place with this water with low energy density. The study evaluated cooling performance on two different days (Exp. 1 and Exp. 2) and at two different cooling water flow rates. The efficiency of the PV system was found to be 8.33 +/- 0.44% in Exp. 1 and 8.3 +/- 0.44% in Exp. 2. The cooling loads of the cooled buildings differ in Exp. 1 and Exp. 2 due to ambient conditions. The cooling load in Exp. 1 was determined to be 572 +/- 22.8 W and in Exp. 2 about 828 +/- 33.1 W. The heat loads extracted from the building by the groundwater used as a cooling fluid are 410 +/- 16.4 W and 786 +/- 31.4 W for Exp. 1 and Exp. 2. The cooling performance evaluation criteria (CPEP) value was found to be 0.72 for Exp. 1 and 0.95 for Exp. 2. Although there was a significant difference between the cooling loads for Exp. 1 and Exp. 2, the cooling load coverage increased with the increase in cooling water flow rate according to the CPEP values. Although in both experiments the cooling load was not fully met and the temperature inside the structure rose slightly during the experiment, it was kept cool.
Keywords: Solar water pumping; Space cooling; Cooling performance; Efficiency